Fundamental interactions : (World Scientific, 2003)
Contents: Proceedings of the Seventeenth Lake Louise Winter Institute, Fundamental Interactions, held from February 17-23, 2002 at the Chateau Lake Louis, Alberta, Canada. Material is devoted to the most recent developments in QCD and electroweak physics.